FUTURE PSYCHOLOGISTS’ SELF-ATTITUDE AS A FACTOR OF PROFESSIONAL SELF-DEVELOPMENT - Didyk, Nataliia; Onufriieva, Liana (PSYCHOLOGICAL JOURNAL, 2019)
The peculiarities of future psychologists’ self-attitudes are considered as an important factor in their professional self-development. Self-attitude is a certain stable feeling towards e personal Self, which contains a number of specific modalities (measurements) that differ both in emotional tone, experience, as well as in the semantic sense of the corresponding attitude to oneself. The structure of self-attitude is described; it is represented by the emotional component (self-perception) and the self-estimating component. The basic functions of self-attitude are revealed: self-reflection, self-expression and self-realization, preservation of internal stability and continuity of Self, self-regulation and self-control, psychological protection, and intra-communications. The experimental study included the following methods: questionnaire on self-attitude of V.V. Stolin and S.R. Pantylieiev; self-actualization test of E. Shostrom; author's technique of indirect measurement of self-assessments to determine a character of the respondents' emotional and appraisal attitude towards their own professional self-images; D. Campbell’s Self-Concept Clarity Scale. It is experimentally proved that future psychologists’ self-attitude is characterized mainly by an average level of self-acceptance, self-management, openness, self-confidence. The future psychologists imagine their personality, character and activities mostly with respect and sympathy; they are interested in personal Self, have a sense of the value of their own personality. They are characterized by increased reflection, deep penetration into oneself, awareness on their own difficulties, adequate self-images and absence of suppression. Sometimes, the future psychologists are characterized by their self-concept rigidity, fixation, and the reluctance to change oneself against the background of a general positive attitude towards oneself. Some students are characterized by self-accusation, readiness to blame themselves for their failures or drawbacks, lack of sympathy for themselves.